Upaya Meningkatkan Keterampilan Membaca Al-Qur’an dengan Metode Al Baghdadi - Zakaria, Syifa Azizah; Fatimah, Titim; Rahman, Alvin Yanuar (Indonesian Journal of Islamic Elementary Education, 2024)
Low Qur'an reading skills can be caused by several factors, such as lack of teacher competence, limited learning time, ineffective learning methods, and an unsupportive family environment. This study aims to determine the Qur'an reading skills of fifth grade students of MI Al-Misbah, Bandung Regency using the Al Baghdadi method. This study uses Classroom Action Research (CAR) with two cycles, each cycle consisting of two actions with four stages, namely planning, action, observation, and reflection with a mix method approach, namely qualitative and quantitative. Data were collected through observation, reading tests, and documentation. The results showed that there was an increase after applying the Al Baghdadi learning method, in cycle I, the classical completion rate of students reached 42% with a sufficient category. However, in cycle II, the classical completion rate increased to 81% with a very good category. It can be concluded that the use of the Al Baghdadi learning method is effective in improving the Qur'an reading skills of fifth grade students at Madrasah Ibtidaiyah Al-Misbah.